Безупречная репутация - Маринина Александра Борисовна (А. Маринина, 2021)
Экземпляры: СБ (20210622) / Инвентарный номер: 61200 / Цена: 381.00 / Сис.шифр: Р2 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6